Hormetic changes by gamma 60Co radiation effect in chille apaxtleco M1 plants - Croseños- Palazin, Martha Isela; Antúnez-Ocampo, Oscar Martín; Sabino-López, Juan Elías; Espinosa-Rodríguez, Mariana; Cruz-Izquierdo, Serafín Cruz-Izquierdo (Ecosistemas y Recursos Agropecuarios, 2023)
The state of Guerrero has a great diversity of native chiles that are used locally and regionally, among them, the apaxtleco chili. The objective of the research was to evaluate the effects of radiation to the seed with gamma rays 60Co in morphological aspects, yield parameters and quality of the fruit of M1 plants of three phenotypes of apaxtleco chili. The combination of radiation doses (0, 50, 100, 150, 200, 250 and 300 Gy) with the three chili phenotypes resulted in 21 treatments, which were distributed in a completely randomized design with six replications. Gamma radiation did not affect the height, stem diameter and branch formation, nor yield components (number and weight of fruits) of the plants In quality of the fruit; intermediate doses (100 to 200 Gy) increased the weight (fresh and dry) and diameter (polar and equatorial) of the fruits; whereas, high doses reduced seed formation. However, the interaction of radiation doses with the chili phenotype showed statistical significance (α ≤ 0.05) in growth, yield and fruit quality; since the smooth width presented plants with greater height and number of branches; while Chinese Width 1 and 2 had higher yield and fruit size. Individuals resulting from seeds treated with 100 to 200 Gy can be used in future genetic improvement research for the selection and production of variants of economic importance.